Peran Buruh Tani Perempuan Dalam Meningkatkan Perekonomian Keluarga: (Studi Kasus Buruh Cungkil Kelapa di Desa Pengalihan Kecamatan Keritang Kabupaten Indragiri Hilir) - Nana Hardiana; T. Romi Marnelly (Penerbit Jurnal Indonesia, 2025)
This research was conducted in Pengalihan Village, Keritang District, Indragiri Hilir Regency with the aim of finding out the role of women in improving the family economy by workers who contribute to gouging work. The research subjects in this study used the Purposive Sampling technique. This research uses qualitative methods by collecting data through interviews and documentation. The subjects in this research were 5 people, 1 (Key Informant) and 4 coconut chip workers. The theory used is role theory. The results of the research show that female jobber workers in Pengalihan Village have quite a big role in improving their family's economy, so that they can fulfill household needs such as completing household equipment, children's school fees and including their savings. With women's contribution to meeting family needs, the economy is quite stable because the income of jobbers starts from IDR. 2,000,000 - Rp. 5,000,000 within 3 months and depending on how much they do, workers with that kind of income can help their husbands earn a living.